Koncepcja sprawiedliwości Leona Petrażyckiego na tle współczesnej filozofii prawa - Szymaniec, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of present paper is, on the one hand, to reconstruct Leon Petrażycki’s views on justice, and on the other hand, to link them to the contemporary discussion on this subject. Petrażycki’s analysis of justice is purely of descriptive character, i.e. it shows what the nature of justice is and why it should be treated as a legal phenomenon. Critical element is a special strength of Petrażycki’s view. The Polish legal philosopher showed with remarkable clarity why he considered justice not only as a purely subjective category of legal psychology (and therefore, belonging to the sphere of intuitive law), but as a result of emotional projection, which means that all judgments that attribute justice to specific legislative acts or decisions concerning the application of law were based on a specific illusion. Petrażycki, however, did not accept a relativistic position because he introduced the ideal of universal love in his theory.